Competencies of school heads, teachers performance and students' academic achievement - Sodipe, Rosalia Santarromana (2006)
This reasearch aimed to determine administrators' competencies and their effects on teachers' performance and students' academic achievement in selected secondary schools in the urban and rural settings. Questionnaires and rating scales as well as the results of the National Achievement Test were used to gather data from the respondents. Multiple regressions were used in addressing the effect of personal data on administrators' competencies and their effects on teachers' competencies and students' achievement rate. It was concluded that a significant relationship exists between the administrators' competencies and teachers' performance. School heads in top schools are competent in moral and ethical practices, communication skills, and networking and human relation skills. Only their age affects students' academic achievement.